1995
DOI: 10.1007/bf00223282
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mapping of soybean cyst nematode race-3 resistance loci in the soybean PI 437.654

Abstract: Resistance to the soybean cyst nematode (SCN) (Heterodera glycines Ichinohe) is difficult to evaluate in soybean [Glycine max (L.) Merr.] breeding. PI 437.654 has resistance to more SCN race isolates than any other known soybean. We screened 298 F6∶7 recombinant-inbred lines from a cross between PI 437.654 and 'BSR101' for SCN race-3 resistance, genetically mapped 355 RFLP markers and the I locus, and tested these markers for association with resistance loci. The Rhg 4 resistance locus was within 1 cM of the I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
159
0
7

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(181 citation statements)
references
References 28 publications
15
159
0
7
Order By: Relevance
“…Differentials and susceptible control were used as monitor the SCN populations and their responses remained consistent while no race shifts occurred. The FI values distribution for each SCN race (Figure 1 A and B) shows that the resistance to SCN in soybean is a quantitative trait, as reported by other researchers (Mansur et al, 1993;Concibido et al, 1994;Webb et al, 1995;Yue et al, 2001). Table 1.…”
Section: Resultssupporting
confidence: 76%
See 1 more Smart Citation
“…Differentials and susceptible control were used as monitor the SCN populations and their responses remained consistent while no race shifts occurred. The FI values distribution for each SCN race (Figure 1 A and B) shows that the resistance to SCN in soybean is a quantitative trait, as reported by other researchers (Mansur et al, 1993;Concibido et al, 1994;Webb et al, 1995;Yue et al, 2001). Table 1.…”
Section: Resultssupporting
confidence: 76%
“…Soybean cyst nematode (Heterodera glycines Ichinohe -SCN) is a pathogen that affects soybean production worldwide with losses that reached 9 million tons in 1998 (Wrather et al, 2001). Sources of resistance to SCN were reported first by Ross (Ross & Brim, 1957).…”
Section: Introductionmentioning
confidence: 99%
“…De acordo com Webb et al (1995), esta região apresenta-se associada com caracteres relacionados à tolerância a nematóides formadores de galhas, e para Mansur et al (1998), a região também esta associada a stresse causado na planta por fatores ambientais, entre eles à tolerância a seca.…”
unclassified
“…According to Falconer and Mackay (1996), heritability estimates depend on the plant material, the estimation method and the experiment. Webb et al (1995) reported a broad-sense heritability of 97% for resistance to race 3 in crosses with PI 437654.…”
Section: Phenotypic Evaluation Of the Selected Populationsmentioning
confidence: 99%
“…One of the QTL with major effect in LG G, designated rhg1, confers resistance to several races (Chang et al 1997, Concibido et al 1997, Meksem et al 2001, Yue et al 2001, Glover et al 2004, Silva et al 2007b, while another in LG A2 (Rhg4), with major effect, confers specific resistance to race 3 (Mahalingam and Skorupska 1995, Webb et al 1995, Chang et al 1997, Meksem et al 2001). …”
Section: Introductionmentioning
confidence: 99%